Immunohistochemical distribution of ghrelin, obestatin and leptin hormones in the abomasum of hair goat - Zelal Karakoç; Uğur Topaloğlu; Muzaffer Aydın Ketani (Eurasian Journal of Veterinary Sciences)
Aim: Ghrelin, obestatin and leptin hormones are called appetite regulating hormones. It reported that ghrelin initiates feeding, obestatin suppresses appetite and leptin gives a feeling of fullness. In human and other mammalian species, studies have reported that ghrelin, obestatin and leptin are expressed at different concentrations from all parts of the stomach. The present study was conducted to determine the expression of ghrelin, obestatin and leptin hormones in hair goat abomasum. Materials and Methods: The abomasum tissues for the study were obtained from 6-8-month-old kids and were collected from cardia, fundus and pylorus regions of the animals abomasums. The ghrelin, obestatin and leptin immunohistochemical staining methods were used, which were applied to all of the sections following the routine histological process. Results: The immunoreactivity of ghrelin, obestatin and leptin was found to be different in all parts of the abomasum. Immunoreactivity was found to be dispersed settlement the abomasum in the cardia region. According to the mean H score, it was determined that ghrelin, obestatin and leptin were intensely expressed in the cardia, pilorus and fundus regions. Conclusion: The appetite hormones (ghrelin, obastatin and leptin) were expressed at different concentrations from the cardia, fundus and pilorus regions in the abomazum, suggesting that these hormones perform similar functions in hair goats considering their physiological effects on feed intake. More research is needed to about use of animal nutrition of ghrelin, obestatin and leptin hormones.